Woman, man, and God in modern Islam - Friend, Theodore (Wm. B. Eerdmans Pub. Co, 2012)
"Award-winning historian Theodore Friend recently set out alone across Asia and the Middle East on a quest to understand firsthand the life situations of women in Indonesia, Pakistan, Saudi Arabia, Iran, and Turkey. Woman, Man, and God in Modern Islam recounts Friend's remarkable journey and relates hundreds of encounters and conversations with people he met along the way. Commingling a deep respect for Islam and his faith in the potential of women to change their worlds, Friend presents an open, exploratory outsider's perspective on women in five very different Islamic cultures -- timely fare for all who wish to broaden their world horizons."--Publisher's description